COMPLICATIONS OF ORAL INJURIES IN YOUNG CHILDREN (Conferencea, 2024)
No child has ever grown up without scratches, abrasions and even fractures. Children's cognition and curiosity are a predisposing factor for injury. The main task of parents is to take timely measures, provide first aid and not lose their cool head. It is these factors that will determine the consequences and complications.